1997
DOI: 10.1007/s002340050495
|View full text |Cite
|
Sign up to set email alerts
|

MRI of autosomal dominant pure spastic paraplegia

Abstract: We examined 16 patients with autosomal dominant pure spastic paraplegia (HSP) and 15 normal controls matched for age and sex using MRI of the brain and spinal cord. Images were assessed qualitatively by two independent radiologists, blinded to the clinical diagnosis. Areas of the brain and corpus callosum on one midsagittal slice and the area of the brain on one axial slice were measured and a "corpus-callosum index" expressing the size of the corpus callosum relative to that of the brain was calculated. Cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 13 publications
4
27
1
1
Order By: Relevance
“…Spinal atrophy has been observed in groups of individuals with pathologies such as autosomal dominant leukodystrophy, amyotrophic lateral sclerosis and hereditary paraplegia. [5][6][7] Good correlation between spinal cord area (SCA) and a number of global clinical scores has also been found in several studies of patients with multiple sclerosis in cross-sectional as well as longitudinal settings. 8 It is not known whether a similar quantitative relation between spinal cord atrophy and the extent of disability is found in individuals with SCI.…”
Section: Introductionmentioning
confidence: 95%
“…Spinal atrophy has been observed in groups of individuals with pathologies such as autosomal dominant leukodystrophy, amyotrophic lateral sclerosis and hereditary paraplegia. [5][6][7] Good correlation between spinal cord area (SCA) and a number of global clinical scores has also been found in several studies of patients with multiple sclerosis in cross-sectional as well as longitudinal settings. 8 It is not known whether a similar quantitative relation between spinal cord atrophy and the extent of disability is found in individuals with SCI.…”
Section: Introductionmentioning
confidence: 95%
“…When the SI was higher in white than in gray matter, the white matter SI was considered pathologic. Spinal cord anteroposterior and coronal diameters and cross-sectional areas were measured at the C2, T6, and T11 levels on the screen of a workstation, as described by Krabbe et al, 10 and the measures were compared with those in their healthy controls (n ϭ 15; ages; 24 -61 years). The measures out of the range of 2 SDs were considered pathologic.…”
Section: Mr Imaging Examinationsmentioning
confidence: 99%
“…All the anteroposterior and coronal diameters and the cross-sectional areas were significantly smaller than those in the control material (ie, out of the 2 SD range). The measurements and the control values from the literature 10 are presented in the Table. …”
Section: Measurements Of the Spinal Cordmentioning
confidence: 99%
“…[3][4][5] The radiologic findings of HSP are nonspecific, including mild-to-moderate brain atrophy, thinning of the corpus callosum, nonspecific white matter lesions in the cerebral hemispheres, abnormal T2 high signal intensity in the posterior limb of the internal capsules, and atrophy of the spinal cord. [3][4][5][6][7][8][9][10] Pathologic studies have shown that the corticospinal tracts, which route through the posterior limb of the internal capsules on their way to the brain stem and spinal cord, are the main tracts involved in HSP. Recently, in brain MR imaging of 2 unrelated patients with autosomal recessive HSP, we found high signal intensities in the posterior limb of the internal capsules bilaterally in the anatomic location of the corticospinal tracts.…”
mentioning
confidence: 99%